2008
DOI: 10.1523/jneurosci.0384-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Calcium-Permeable AMPA Receptors during Synaptic Potentiation Is Regulated by CaM-Kinase I

Abstract: Ca2ϩ -permeable AMPA receptors (CP-AMPARs) at central glutamatergic synapses are of special interest because of their unique biophysical and signaling properties that contribute to synaptic plasticity and their roles in multiple neuropathologies. However, intracellular signaling pathways that recruit synaptic CP-AMPARs are unknown, and involvement of CP-AMPARs in hippocampal region CA1 synaptic plasticity is controversial. Here, we report that intracellular infusion of active CaM-kinase I (CaMKI) into cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
154
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(168 citation statements)
references
References 75 publications
5
154
2
1
Order By: Relevance
“…Supporting this notion, theta burst stimulation led to the transient synaptic appearance of GluR2-lacking AMPARs (16) and required postsynaptic SNARE-dependent exocytosis (6,10); but high-frequency, stimulation-induced LTP is mediated by synaptic addition of GluR2/3-containing AMPARs (43) and not GluR2-lacking AMPARs (ref. 16, but see ref. 15), and does not require exocytosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this notion, theta burst stimulation led to the transient synaptic appearance of GluR2-lacking AMPARs (16) and required postsynaptic SNARE-dependent exocytosis (6,10); but high-frequency, stimulation-induced LTP is mediated by synaptic addition of GluR2/3-containing AMPARs (43) and not GluR2-lacking AMPARs (ref. 16, but see ref. 15), and does not require exocytosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, stimulation of hippocampal neurons with BDNF also increased the synaptic accumulation of GluA1 AMPA receptor subunit, by a mechanism dependent on mTOR and Ca 2þ -and calmodulin-dependent protein kinase kinase (CaMKK) (Caldeira et al, 2007a;Fortin et al, 2012;Guire et al, 2008). BDNF also upregulated GluA1 protein levels in rat forebrain synaptoneurosomes, further indicating that the neurotrophin induces local translation of AMPA receptors at the synapse (Schratt et al, 2004).…”
Section: Bdnf-induced Changes In the Neuronal Proteomementioning
confidence: 95%
“…In addition to the proteins identified in the proteomics analysis discussed above, target oriented studies have shown effects of BDNF in total expression of AMPA and NMDA receptor subunits in cultured hippocampal and cortical neurons (Caldeira et al, 2007a(Caldeira et al, , 2007bFortin et al, 2012;Guire et al, 2008;Narisawa-Saito et al, 1999;Small et al, 1998). Interestingly, stimulation of hippocampal neurons with BDNF also increased the synaptic accumulation of GluA1 AMPA receptor subunit, by a mechanism dependent on mTOR and Ca 2þ -and calmodulin-dependent protein kinase kinase (CaMKK) (Caldeira et al, 2007a;Fortin et al, 2012;Guire et al, 2008).…”
Section: Bdnf-induced Changes In the Neuronal Proteomementioning
confidence: 99%
“…Infusion of active CaMKI potentiates AMPARs in cultured neurons through synaptic incorporation of CP-AMPARs, in a manner that requires actin polymerisation. Furthermore, in slices, CA3-CA1 LTP induced by theta burst stimulation recruited CP-AMPARs, and this was prevented by inhibition of CaMKK, an upstream activator of CamKI 141 . However, as yet, the targets of CamKI that mediate synaptic expression of CP-AMPARs have not been identified.…”
Section: Ampar Phosphorylationmentioning
confidence: 98%
“…Together, these data highlight the critical importance of GluA1-S845 phosphorylation in controlling the availability of synaptic CP-AMPARs. Intriguingly, although it does not directly phosphorylate AMPAR subunits, CaMKI has also been implicated in CP-AMPAR expression during hippocampal LTP 141 . Infusion of active CaMKI potentiates AMPARs in cultured neurons through synaptic incorporation of CP-AMPARs, in a manner that requires actin polymerisation.…”
Section: Ampar Phosphorylationmentioning
confidence: 99%